2010
DOI: 10.1103/physrevlett.104.187201
|View full text |Cite
|
Sign up to set email alerts
|

Manipulation of Spin Transport in Graphene by Surface Chemical Doping

Abstract: The effects of surface chemical doping on spin transport in graphene are investigated by performing nonlocal measurements in ultrahigh vacuum while depositing gold adsorbates. We demonstrate manipulation of the gate-dependent nonlocal spin signal as a function of gold coverage. We discover that charged impurity scattering is not the dominant mechanism for spin relaxation in graphene, despite its importance for momentum scattering. Finally, unexpected enhancements of the spin lifetime illustrate the complex nat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
179
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(188 citation statements)
references
References 32 publications
8
179
1
Order By: Relevance
“…1(f). After the Bi-cluster deposition, the carrier mobility was reduced because the clusters contributed scattering centers, as reported in previous experiments [22][23][24]. The transport parameters of the graphene before and after the Bi-cluster deposition are detailed in Table 1.…”
Section: Resultsmentioning
confidence: 53%
“…1(f). After the Bi-cluster deposition, the carrier mobility was reduced because the clusters contributed scattering centers, as reported in previous experiments [22][23][24]. The transport parameters of the graphene before and after the Bi-cluster deposition are detailed in Table 1.…”
Section: Resultsmentioning
confidence: 53%
“…This contrasts with previous studies, which have demonstrated that although charged impurities affect the carrier mobility, they do not affect spin relaxation. 10,36,37 This suggests that although we are decreasing the concentration of charge scatterers in our devices via the encapsulation process, we are also unintentionally decreasing the source of spin scattering in the device. For instance, this source could be magnetic scatterers that have recently been predicted to increase the spin flipping process without having a significant influence on the charge transport.…”
Section: Spin Transport In Bilayer Graphenementioning
confidence: 99%
“…5,6 The initial spin transport studies were mainly performed on single-layer [7][8][9][10] and bilayer exfoliated graphene, 9,11 and large-area graphene [12][13][14][15] deposited on conventional SiO 2 substrates. Although enhanced spin-relaxation times have been reported for bilayer graphene-based devices compared with those based on a single layer, the relatively low spin diffusion constants overall yield a lower spin-relaxation length of only 1-2 μm, 9,11 far below the theoretical predictions.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, spin relaxation in graphene structures has been a baffling problem [3]. While experiments in both single layer graphene (SLG) [4][5][6][7][8][9][10][11] and bilayer graphene (BLG) [7,8] yield spin lifetimes on the 100-1000 ps time scale (the highest values achieved in graphene/h-BN structures [12,13]), theories based on realistic spin-orbit coupling and transport parameters predict lifetimes on the order of microseconds [14][15][16][17][18][19][20][21][22][23][24].While the magnitudes of the spin-relaxation rates of SLG and BLG are similar, the dependence of the rates on the electron density is opposite in the two systems. In SLG the spin-relaxation rate decreases with increasing the carrier density [5][6][7][8], in BLG the spin-relaxation rate increases [7,8].…”
mentioning
confidence: 99%